Genome-Wide Analysis of the Polyphenol Oxidase Gene Family in Olea europaea Provides Insights into the Mechanism of Enzymatic Browning in Olive Fruit - Qingqing Liu; Chenhe Wang; Qizhen Cui; Yutong Fan; Jianguo Zhang; Guodong Rao (MDPI AG, 2023)
Browning of olive (Olea europaea L.) fruit reduces the sensory and nutritional qualities of olive oil, thereby increasing production costs. Polyphenol oxidases (PPOs) are the key enzymes that catalyze phenolic substance oxidation and mediate enzymatic browning in olive fruit, but the exact regulatory mechanism remains unclear. The main challenge is the lack of comprehensive information on OePPOs at the genome-wide level. In this study, 18 OePPO genes were identified. Subsequently, we performed a bioinformatic analysis on them. We also analyzed the expression patterns and determined the relationship among browning degree, PPO activity, and expression of OePPOs in the fruits of three olive varieties. Based on our analysis, we identified the four most conserved motifs. OePPOs were classified into two groups, with OePPOs from Group 1 showing only diphenolase activity and OePPOs from Group 2 exhibiting both mono-/diphenolase activities. Seven pairs of gene duplication events were identified, and purifying selection was found to have played a critical role in the evolution of the OePPO gene family. A positive correlation was observed between the browning degree of olive fruit and PPO activity across different olive varieties. Moreover, two important genes were found: OePPO-5 the main effector gene responsible for fruit browning, and OePPO-8, a key gene associated with specialized metabolite synthesis in the olive fruit. In short, our discoveries provide a basis for additional functional studies on OePPO genes and can help elucidate the mechanism of enzymatic browning in olive fruit in the future.